Seraphina : a novel - Hartman, Rachel (New York : Random House, 2012)
In a world where dragons and humans coexist in an uneasy truce and dragons can assume human form, Seraphina, whose mother died giving birth to her, grapples with her own identity amid magical secrets and royal scandals, while she struggles to accept and develop her extraordinary musical talents.
In a world where dragons and humans coexist and dragons can assume human form, Seraphina, whose mother died giving birth to her, grapples with her own identity while she struggles to accept and develop her musical talents.
Keywords: Identity -- Fiction; Self-actualization (Psychology) -- Fiction; Dragons -- Fiction; Secrets -- Fiction; Music -- Fiction; Courts and courtiers -- Fiction; Fantasy; Identity (Psychology) -- Fiction; Self-realization -- Fiction; Dragons -- Fiction; Secrecy -- Fiction; Music -- Fiction; Courts and courtiers -- Fiction; Fantasy fiction